(untitled) (Research, Society and Development, 2022)
The present work sought to evaluate the use of natural sunlight in the removal of methylene blue dye from aqueous solutions through heterogeneous photocatalysis using TiO2 (Degussa P25) nanoparticles as a catalyst, since this is a dye widely used industrially. In the study, the influence of catalyst concentration (0; 0.25; 0.5 and 0.75 g/L) and pH (3, 5 and 8) of the solution on the dye removal efficiency after sun exposure was verified for 2 hours under magnetic stirring. For this, absorbance reading was used in a UV-vis spectrophotometer, at pre-established time intervals. It was possible to verify high efficiency of dye removal, reaching values above 90% in all the conditions tested (except in the absence of catalyst and magnetic stirring). In addition, it was possible to observe that both the catalyst concentration and the pH of the solution had an influence on the dye removal efficiency, where, for the analyzed concentrations, it was evidenced that an increase in the concentration from 0.25 to 0.75 g/L resulted in an increase in removal from 91.5% to 99.5% after 2 hours of sun exposure. It was also observed that the reduction of the pH from 8 to 3 resulted in an increase in the dye removal rate, where with pH 3 and 30 min of exposure, more and 90% of removal was achieved. From the results, it appears that photocatalysis using sunlight is an economical and sustainable alternative to reduce environmental pollution caused by this dye.